Ethnic Media in the Digital Age, Sherry S. Yu and Matthew D. Matsaganis (eds) (2019). (1st June 2020) - Bashri, Maha
Ethnic Media in the Digital Age, Sherry S. Yu and Matthew D. Matsaganis (eds) (2019)New York: Routledge, 216 pp., ISBN 978-1-13848-648-5, h/bk, 129.78ISBN 978-1-351045-31-5, e-book, 57.95